2019
DOI: 10.1038/s41378-019-0097-7
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness and ATP recovery of stored red blood cells in serum

Abstract: In transfusion medicine, there has been a decades-long debate about whether the age of stored red blood cells (RBCs) is a factor in transfusion efficacy. Existing clinical studies investigating whether older RBCs cause worse clinical outcomes have provided conflicting information: some have shown that older blood is less effective, while others have shown no such difference. The controversial results could have been biased by the vastly different conditions of the patients involved in the clinical studies; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
(65 reference statements)
1
25
0
Order By: Relevance
“…Finally, to obtain the intracellular ATP concentration, the average measured concentration was normalized by the total number of cells lysed and the mean volume obtained in previous experiments. ATP measured concentrations were similar to previous studies52 .RBCs recirculation and crossingtime determination. Flow was driven through the device at a fix flow rate (100µl/h) using a peristaltic pump (IPC, ISMATEC) (Suppl Fig 1F); wider channels (5 m) were added at both sides of the microchannel array to ensure that microchannel clogging by stuck RBCs did not significantly affect the pressure difference across the array.…”
supporting
confidence: 89%
“…Finally, to obtain the intracellular ATP concentration, the average measured concentration was normalized by the total number of cells lysed and the mean volume obtained in previous experiments. ATP measured concentrations were similar to previous studies52 .RBCs recirculation and crossingtime determination. Flow was driven through the device at a fix flow rate (100µl/h) using a peristaltic pump (IPC, ISMATEC) (Suppl Fig 1F); wider channels (5 m) were added at both sides of the microchannel array to ensure that microchannel clogging by stuck RBCs did not significantly affect the pressure difference across the array.…”
supporting
confidence: 89%
“…And although there are conflicting data (Weed et al, 1969;Karger et al, 2012;Huisjes et al, 2018) on the relationship between intracellular ATP content and RBC deformability, some authors have tested the effectiveness of restoring the expected level of ATP in reducing PRBC stiffness. Thus, Xu et al (2019) examined whether stiffness of PRBCs can be restored in human serum (at temperatures below 37 • C) and the role of storage duration in this process. Authors demonstrated that PRBCs could recover their deformability and ATP concentration in human serum, with the extent of recovery decreasing as a function of storage duration (Xu et al, 2019).…”
Section: Reversibility Of Storage-related Impairment In Rbc Deformabilitymentioning
confidence: 99%
“…Thus, Xu et al (2019) examined whether stiffness of PRBCs can be restored in human serum (at temperatures below 37 • C) and the role of storage duration in this process. Authors demonstrated that PRBCs could recover their deformability and ATP concentration in human serum, with the extent of recovery decreasing as a function of storage duration (Xu et al, 2019). Moreover, the recovery processes took place on a scale of tens (10 -90 min) of minutes, and in the case of a more extended storage period, a longer recovery was required.…”
Section: Reversibility Of Storage-related Impairment In Rbc Deformabilitymentioning
confidence: 99%
“…The RBC cytoskeleton deforms generally passively. Only one complex is actively triggered [ 54 ]. ATP production in RBCs depends on the availability of glucose as substrate and on the enzymatic activity of the Embden–Meyerhof pathway.…”
Section: Discussionmentioning
confidence: 99%